Epidemiology of contagious bovine pleuropneumonia in Kelantan and Terengganu, Malaysia - Mohamed, Zarina (2016)
Contagious Bovine Pleuropneumonia (CBPP) is a highly infectious disease of cattle caused by Mycoplasma mycoides subsp. mycoides Small Colony (MmmSC). CBPP is one of the diseases recognized by OIE that needs to be controlled or eradicated through surveillance program. Therefore, the objectives of this study were to determine the seroprevalence and risk factors of CBPP in cattle and to isolate and detect the agent of CBPP from cattle in Kelantan and Terengganu. Data from National Serological Surveillance in 2013 and data from Kota Bharu Regional Veterinary Laboratory in 2011 to 2014 conducted by DVS were retrieved and analysed for seroprevalence and samples of nasal swab from farms and samples of organ from abattoirs were collected for mycoplasma isolation and detection of MmmSC. A total of 3,242 sera from 428 cattle farms were tested for CBPP using the competitive ELISA (c-ELISA) to detect specific antibodies. The overall animal-level seroprevalence of CBPP in nine states in Peninsular Malaysia between 2011 and 2014 was 8% (266/3,242) and the herd seroprevalence was 17% (75/428). The animal-level seroprevalence ranged between 5% (46/917) in Terengganu and 9% (220/2,325) in Kelantan whereas the herd prevalence ranged between 12% (22/210) in Terengganu and 24% (53/218) in Kelantan. Risk factors were identified in terms of farm location and animal characteristics such as farm location, age, sex, breeds and production system. A total of 204 nasal swabs from 18 sero-positive cattle herds in Kelantan were collected for isolation of MmmSC. One hundred and sixty three (163) lungs and mediastinal lymph nodes from cattle slaughtered in abattoirs in Kelantan were collected for isolation of MmmSC. Detection of MmmSC from broth and agar was by polymerase chain reaction (PCR) and detection of antigen from organs was by immunoperoxidase (IP). Out of the 326 samples of nasal swab, lung and mediastinal lymph node, 41 (12.5%) samples showed turbidity in the pleuropneumonia-like-organism (PPLO) broth and 15 (9.2%) of the lung and mediastinal lymph node samples had ‘fried-egg colony’ growth on the PPLO agar. The 41 suspected cultures in broth and the 15 suspected colonies on agar were subjected to PCR but was negative. Nevertheless, 2 (1.2%) of the lung samples showed lesions suggestive of MmmSC infections, which included widening of the interlobular septa and hepatization of the lung parenchyma with mixture of oedematous fluid and fibrin. Similarly, no positive reaction was observed in any of these organ samples following immunoperoxidase staining. In conclusion, the cattle in Kelantan and Terengganu were exposed to MmmSC due to seropositive of c-ELISA however MmmSC was not detected in any of the samples, indicating the absence of the organism in the cattle of Kelantan and Terengganu.